2004
DOI: 10.1021/bp0498746
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation, Monitoring, and Analysis of Pathway Dynamics by Metabolic Profiling in the Aromatic Amino Acid Pathway

Abstract: Using a concerted approach of biochemical standard preparation, analytical access via LC-MS/MS, glucose pulse, metabolic profiling, and statistical data analysis, the metabolism dynamics in the aromatic amino acid pathway has been stimulated, monitored, and analyzed in different tyrosine-auxotrophic L-phenylalanine-producing Escherichia coli strains. During the observation window from -4 s (before) up to 27 s after the glucose pulse, the dynamics of the first five enzymatic reactions in the aromatic amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 61 publications
(45 reference statements)
2
47
0
Order By: Relevance
“…It is interesting that our production data and SRM analysis are consistent with a previous study in which pulse-feeding experiments and statistical analysis identified AroB, AroA, and AroL as promising metabolic engineering targets to alleviate flux control in L-phenylalanine-producing strains (32). In our study, we demonstrated, using the shikimate operons, that AroB expression remained relatively low unless its first 15 codons were optimized.…”
Section: Discussionsupporting
confidence: 90%
“…It is interesting that our production data and SRM analysis are consistent with a previous study in which pulse-feeding experiments and statistical analysis identified AroB, AroA, and AroL as promising metabolic engineering targets to alleviate flux control in L-phenylalanine-producing strains (32). In our study, we demonstrated, using the shikimate operons, that AroB expression remained relatively low unless its first 15 codons were optimized.…”
Section: Discussionsupporting
confidence: 90%
“…Successful applications cover a broad range of research topics and microbial systems, for example, in vivo NMR [23], optimization of amino acid formation [70,71], investigation of ethanol formation in yeast [72] and beta-lactam antibiotics [73][74][75].…”
Section: Application Of Microbial Metabolomicsmentioning
confidence: 99%
“…The most popular method that is used for microbial cells, is quenching with cold methanol, maintaining the sample temperature below -20 o C, followed by collection of the cells by a centrifugation step prior to extraction (19). This approach has been originally developed and applied for yeast, but has later also been used in studies of different bacteria (4,5,21,23,26,49,50). For animal and plant cells liquid nitrogen is commonly utilized for quenching (43).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Knowledge about the changes of the intra-cellular metabolite concentrations offers a direct access to the identification of enzymatic kinetics especially to the in vivo kinetics of the underlying metabolic network, (4,7,28,33,44,45,46) or may elucidate limiting or inhibiting biosynthetic steps, which can be used for iterative strain optimisation (26).…”
Section: Introductionmentioning
confidence: 99%